2016
DOI: 10.5194/tc-10-1449-2016
|View full text |Cite
|
Sign up to set email alerts
|

Coastal dynamics and submarine permafrost in shallow water of the central Laptev Sea, East Siberia

Abstract: Abstract. Coastal erosion and flooding transform terrestrial landscapes into marine environments. In the Arctic, these processes inundate terrestrial permafrost with seawater and create submarine permafrost. Permafrost begins to warm under marine conditions, which can destabilize the sea floor and may release greenhouse gases. We report on the transition of terrestrial to submarine permafrost at a site where the timing of inundation can be inferred from the rate of coastline retreat. On Muostakh Island in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 32 publications
2
56
2
1
Order By: Relevance
“…The effects of slow thermo-erosion rates along a Yedoma hill and considerably faster rates along alas segments not only comprise ground ice thaw and constant sediment supply from these two major geomorphological and sedimentological units, but also highlight the greater vulnerability of the low-lying drained part of the Ivashkina Lagoon depression to becoming inundated in the future. Regarding permafrost depths in areas close to the shore, Overduin et al [32] suggests that the depth to ice-bonded permafrost close to shore is inclined steeply if the coastline retreat is slow and is inclined shallowly where rapid coastal erosion rates prevail. Although thermo-erosional widening within Ivashkina Lagoon generally proceeds at a slow rate, differences in the rate of widening may also be reflected in the subaquatic permafrost table depth.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of slow thermo-erosion rates along a Yedoma hill and considerably faster rates along alas segments not only comprise ground ice thaw and constant sediment supply from these two major geomorphological and sedimentological units, but also highlight the greater vulnerability of the low-lying drained part of the Ivashkina Lagoon depression to becoming inundated in the future. Regarding permafrost depths in areas close to the shore, Overduin et al [32] suggests that the depth to ice-bonded permafrost close to shore is inclined steeply if the coastline retreat is slow and is inclined shallowly where rapid coastal erosion rates prevail. Although thermo-erosional widening within Ivashkina Lagoon generally proceeds at a slow rate, differences in the rate of widening may also be reflected in the subaquatic permafrost table depth.…”
Section: Discussionmentioning
confidence: 99%
“…Offshore of Muostakh Island, repeated borehole measurements separated by 31–32 years indicated an ice‐bearing subsea permafrost degradation rate of 0.14 m/year (Shakhova et al, ). Furthermore, geoelectric observations offshore of Muostakh Island showed that the degradation rate of ice‐bearing subsea permafrost decreased from 0.4 m/year immediately after inundation to 0.1 m/year 60–110 years after submergence from coastal erosion (Overduin et al, ). The same study also demonstrated that the depth to ice‐bearing subsea permafrost at a given distance perpendicular to shore is inversely correlated with the coastal erosion rate.…”
Section: Study Areamentioning
confidence: 99%
“…For example, offshore boreholes and mean erosion rates derived from historical remote sensing imagery are an effective way to calculate ice‐bearing permafrost degradation rates (Osterkamp & Harrison, ; Rachold et al, ; Shakhova et al, ). If boreholes are not available, geoelectric methods have proven to be effective at mapping the depth to ice‐bearing subsea permafrost (e.g., Overduin et al, , ; Sellmann et al, ) and the depth to permafrost below freshwater thermokarst lakes (e.g., You et al, ). The electrical resistivity tomography method is effective at delineating unfrozen and frozen sediment, because there is an increase in electrical resistivity as water freezes and forms ice (Kneisel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are problems with high attenuation of the reflected seismic signal where sediments contain gas28 and/or reflect variability in permafrost properties2930. Methods based on electrical properties of frozen/unfrozen ground were shown to be applicable in shallow coastal waters3132. Poor knowledge of the physical and chemical processes occurring within subsea permafrost, combined with a lack of observational data for model calibration, restricts further progress in modelling the current state of subsea permafrost and associated methane (CH 4 ) releases in the ESAS1633.…”
mentioning
confidence: 99%